The American Prime Meridian - Grier, David Alan (When Computers Were Human, 2013)
The methods of computation migrated to North America with the navigators who guided the ships across the North Atlantic and the surveyors who delineated the European claims upon the continent. Throughout the eighteenth and nineteenth centuries, the Greenwich Observatory and the British Nautical Almanac served as sources of computational techniques for those traveling west. The observatory had employed Charles Mason before he departed with Jeremiah Dixon to survey the border between Pennsylvania and Maryland.¹ One of the almanac computers, Joshua Moore, emigrated to the United States and corresponded with President Thomas Jefferson on subjects mathematical.² The British Nautical Almanac itself